Macroeconomic Variables and Profitability in the Indonesian Islamic Banking Industry - Mohammad Nur Rianto Al Arif; Rahmi Rahmawati (El Barka, 2021)
Profitability level is one of performance indicator in banking industry, including the Islamic banking industry. The purpose of this study is to analyse the short-run and long-run impact of macroeconomics variables to profitability in the Indonesian Islamic banking industry. The method that used in this paper is vector error correction models (VECM). The variables that used in this paper are industrial production index, inflation, exchange rate, the Bank Indonesia’s rate, and stock exchange composite index. The result shows that in the long-run, all of the macroeconomics variables affect significantly in profitability level. In the short-run, all macroeconomics variables do not  impact the profitability. This result implies that the macroeconomics variable had a time-lag to affect the profitability in the Indonesian Islamic banking industry.